Ontogeny and Early Steps of the Calcification Process in Coralline Algae Lithophyllum corallinae (Florideophyceae, Rhodophyta) - de Carvalho, Rodrigo Tomazetto; Wendt, Camila Hübner Costabile; Willemes, Maria Julia; Bahia, Ricardo da Gama; Farina, Marcos; Salgado, Leonardo Tavares (Frontiers in Marine Science, 2022)
Coralline algae (Rhodophyta, Florideophyceae) are one of the most abundant organisms in the hard-bottom marine photic zone where they provide settlement substrates, structure and shelter on rocky substrates. Coralline algae also play important roles in tropical reefs, both cementing corals together and producing substantial amounts of calcium carbonate. The ecological roles of coralline algae in the marine environment are related to the biomineralization process that occurs in the cell walls. Currently, this group of algae is receiving renewed attention from researchers from different fields, especially due to possible effects of climate changes over its magnesium calcite skeleton. Despite this renewed attention, we still have poor information regarding the first steps of coralline algae ontogeny and calcification. The aim of this study was to describe the earlier steps of Lithophyllum corallinae development and its calcification process. Algae were collected at Vermelha Beach, Rio de Janeiro city. Adult crusts released spores that settled over microscope slides. The germinating spores were analyzed by Polarizing Light Microscopy, Scanning Electron Microscopy, Energy Dispersive Spectroscopy, Transmission Electron Microscopy and Atomic Force Microscopy. Results showed that cell walls mineralization begins at third spore cell division (8 cells specimen), evidenced by changes in light polarization, elemental composition and hardness, restricted to the cell walls of the innermost part of the developing spore.. Nanopores in calcite crystals structure were identified, evidencing macromolecules occlusion, a feature especially important to prevent calcite skeleton cracking in high-energy environments. The beginning of this process could be related to spore size, availability of organic matrix and energy from photosynthesis. All the analysis also confirmed the lack of calcification in the cell walls of the outermost part of the germinating spore, which allows the growth of the individual; but mainly indicates a high level of control in coralline algae mineralization process, representing a relevant information in future studies on coralline algae calcification, including those testing climate changes scenarios.